1995
DOI: 10.1111/j.1432-1033.1995.0827g.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Biological Activities of Lantibiotics with Unique Post‐Translational Modifications

Abstract: Lantibiotics are biologically active peptides which contain the thioether amino acid lanthionine as well as several other modified amino acids. They can be broadly divided into two groups on the basis of their structures : type-A lantibiotics are elongated, amphiphilic peptides, while type-B lantibiotics are compact and globular. In the last decade there has been a marked increase in research interest in these peptides due both to the novel biosynthetic mechanisms by which they are produced, as well as to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(42 citation statements)
references
References 191 publications
(178 reference statements)
0
39
0
3
Order By: Relevance
“…Studies of the role of dlt in rodent infection models showed that this operon was required for host-pathogen interactions involving L. monocytogenes, S. aureus, B. anthracis, and S. agalactiae (1,13,34,78). We show here, for the first time, that the dlt locus of the human opportunistic and entomopathogenic bacterium B. cereus ATCC 14579 is important for protection against insect humoral immune mediators, in- AMPs constitute families of bactericidal peptides widely produced by microbes to inhibit the growth of competing strains (14,81) and by higher organisms as part of the humoral immune response to bacterial infections (42,95). Many AMPs are thought to act by accumulating in the cytoplasmic membrane to a critical concentration allowing the assembly of structures that permeabilize the cell (41,42).…”
Section: Discussionmentioning
confidence: 92%
“…Studies of the role of dlt in rodent infection models showed that this operon was required for host-pathogen interactions involving L. monocytogenes, S. aureus, B. anthracis, and S. agalactiae (1,13,34,78). We show here, for the first time, that the dlt locus of the human opportunistic and entomopathogenic bacterium B. cereus ATCC 14579 is important for protection against insect humoral immune mediators, in- AMPs constitute families of bactericidal peptides widely produced by microbes to inhibit the growth of competing strains (14,81) and by higher organisms as part of the humoral immune response to bacterial infections (42,95). Many AMPs are thought to act by accumulating in the cytoplasmic membrane to a critical concentration allowing the assembly of structures that permeabilize the cell (41,42).…”
Section: Discussionmentioning
confidence: 92%
“…Several roles have been proposed, including acting as a scaffold for the modification enzymes, allowing the prepeptide to be recognized for export, or protecting the producing organism (9). The leader sequences within each lantibiotic class share several conserved residues that could contribute to these functions ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The role(s) of the leader peptide in lantibiotic biosynthesis has been the subject of much speculation (8,9). It may act in a protective role for the producing organism, as its removal is required for bioactivity (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The lantibiotics represent a diverse family of bacterially produced antimicrobial peptides Sahl et al, 1995;van Kraaij et al, 1999). They are characterized by the presence of lanthionine and b-methyllanthionine, which form intramolecular thioether rings.…”
Section: Introductionmentioning
confidence: 99%